A new retrofit approach to the absorption-stabilization process for improving energy efficiency in refineries. (1st January 2017) - Liu, X.G.; He, C.; He, C.C.; Chen, J.J.; Zhang, B.J.; Chen, Q.L.
Abstract: In a refining complex, an absorption-stabilization process used in the production of end-use petro-products (i.e. stable gasoline and liquefied petroleum gas) is energy-intensive and costly. A new absorption-stabilization process with a two-stage condensation section is introduced in this work to further improve energy-use performance. In the new process, a condenser, a condensed oil tank, and a side-reboiler are integrated into the original process and then a heat integration scheme is performed. Compared with the existing process, the proposed process can reduce the cold utility and hot utility by 17.98% and 25.65%, respectively, as well as decrease the total annual operating costs of the heat exchanger network by 17.48%. Additionally, the process retrofit reduces the annual operating costs of cooling water and steam by about $346, 617 at the expense of capital costs around $487, 006, and the corresponding payback period is approximately 17 months. Highlights: Energy analysis is proposed for the existing absorption-stabilization process. A new absorption-stabilization process is presented to reduce energy requirement. A side-reboiler is introduced for the heat integration of the new process. HENs are designed and compared between the existing and new processes.